Characterization of Lignocellulosic Biomass from Malaysian's Yankee Pineapple AC6 Toward Composite Application. Issue 12 (2nd December 2021) - Najeeb, M.I.; Sultan, M.T.H.; Andou, Yoshito; Shah, A.U.M; Eksiler, Kubra; Jawaid, M.; Ariffin, A.H.
ABSTRACT: The aim of this paper is to study the properties of the newly Malaysian pineapple variety, namely, Yankee pineapple's leaf fibers (PALF) biofillers in composite applications. The fibers were extracted from the leaves, which were currently being thrown away or burned down. Comprehensive characterization of Yankee's PALF was carried out to determine its chemical composition, surface morphology, and mechanical, crystallinity, and thermal properties. The results showed that the fiber had a high thermal degradation of 340°C (34% yield). On top of that, the fiber surface elemental composition captures carbon (53.56%) which had the highest atomic percentage followed by oxygen (42.93%) and potassium (3.51%). In addition, the fiber had a rough external surface observed through atomic force microscope analysis, resulting in good compatibility with the matrix polymer. The crystal index of fiber and its size give 55.22% and 2.17-nm values, respectively. Furthermore, 40 mm gauge length of single fiber had the highest tensile strength, which is 420.3 MPa compared to other values of the gauge length.